Incidence of Girl-Child Defilement in Ugbighokho Community South-South Nigeria: The Way Forward - Aghasomwan Bello, Osamuyi; Osunde, Isoken Linda (Mediterranean Journal of Social Sciences, 2022)
This study explores the incidence of girl-child defilement in Ugbighokho Community, South-south Nigeria. The study was guided by the ecological system perspective and the play therapy. The study pointed out some of the socio-economic factors that causes the girl-child defilement which includes, poverty, ignorance, gender inequality and the nature of child’s residence or environment where the child lives. The sample size of this study was 400 using the simple random sampling technique. The cross sectional survey method was adopted for this study. The study established that poverty was the main cause of the girl-child defilement in Ugbighokho Community. The study further revealed that social tie was the main cause for under-reporting of girl-child defilement which in turn has a far-reaching effect on the victim(s). The study therefore recommends poverty alleviation programmes as a means of generating income activities for caregivers in order to prevent them from being compromised by offenders. Received: 21 September 2021 / Accepted: 25 December 2021 / Published: 5 January 2022